Historia de la malacología en México con énfasis en la malacología continental - Naranjo García, Edna (2003)
Late 20th. Century malacology in Mexico represents the fusion of two lines of action from the previous century: natural history museums established in the 18th. Century and field collecting that began in the 16th Century. Museum activity suffered from political influence, mainly in the 19th century. Field work by expeditions from Europe and the USA were important around the 19th century (e.g. the large works by Fischer and Crosse, 1870-1902; von Martens, 1890-1901; Strebel, 1873-1882 and Díaz de León, 1912), but continental mollusc research done by Mexicans was very sporadic (specially in the 19th Century, less in the 20s and 50s of the 20th century) until 1980.